2020
DOI: 10.3389/fendo.2020.00437
|View full text |Cite
|
Sign up to set email alerts
|

MC4R Variant rs17782313 Associates With Increased Levels of DNAJC27, Ghrelin, and Visfatin and Correlates With Obesity and Hypertension in a Kuwaiti Cohort

Abstract: Melanocortin 4 receptor (MC4R), a notable component of the melanocortin system, regulates appetite, body weight, and energy homeostasis. Genome-wide association studies have identified several MC4R variants associated with adiposity; of these, rs17782313, which is associated with increased body mass index (BMI) and overeating behavior, is of particular interest. Another gene associated with increased adiposity in global genome-wide association studies is DNAJC27, a heat shock protein known to be elevated in ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
12
0
2
Order By: Relevance
“…Evidence suggests that this gene is involved in appetite regulation and energy expenditure [ 29 ]. The MC4R rs17782313 variant was associated with the obesity-related proteins ghrelin and visfatin in the Arabic population [ 30 ]. Previous studies showed strong associations of the MC4R rs17782313 variant with higher energy and fat intake and lower carbohydrate and protein intake [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this gene is involved in appetite regulation and energy expenditure [ 29 ]. The MC4R rs17782313 variant was associated with the obesity-related proteins ghrelin and visfatin in the Arabic population [ 30 ]. Previous studies showed strong associations of the MC4R rs17782313 variant with higher energy and fat intake and lower carbohydrate and protein intake [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin has a well-established role in the hypothalamic regulation of appetite. This hormone reduces appetite by decreasing Pro-opiomelanocortin (POMC) neuronal activity and increasing AgRP neuronal activity [ 1 ]. GLP-1 suppresses hunger by activating the glucagon-like peptide 1 receptor (GLP-1R) in the peripheral and central nervous systems, resulting in weight loss [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of some studies were consistent and some were not consistent with the results of this study. The results of a cohort study showed higher ghrelin levels in carriers of C-allele compared to T-allele carriers [ 1 ]. Magno et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that the binding rate of LCN2 and MC4R in the hypothalamus was significantly increased after SG. It is generally believed that the pathogenesis of obesity and related diseases (such as diabetes and hypertension) is closely related to the regulatory role of the central nervous system [ 43 45 ]. The central melanocortin signaling pathway plays a key role, mainly by acting on MC4R.…”
Section: Discussionmentioning
confidence: 99%